2018
DOI: 10.3390/molecules23102541
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from the Stems of Tinospora sinensis and Their Bioactivity

Abstract: Fifty-seven compounds were purified from the stems of Tinospora sinensis, including three new compounds characterized as a lignan (1), a pyrrole alkaloid (11), and a benzenoid (17), respectively. Their structures were elucidated and established by various spectroscopic and spectrometric analytical methods. Among the isolates, fifteen compounds were examined for their anti-inflammatory potential in vitro. The results showed that several compounds displayed moderate inhibition of N-formyl-methionyl-leucyl-phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 61 publications
0
11
0
1
Order By: Relevance
“…A total of 2667 features were detected in both positive and negative ionization modes. By analyzing the MS1 and MS1 mass spectra of the analyte peaks, 58 metabolites were successfully identified using data from previous studies and databases (Table 2) (Ahmad et al, 2016; Bowen & Motawe, 1985; Choudhary, Ismail, Ali, et al, 2010; Choudhary, Ismail, Shaari, et al, 2010; Dong et al, 2010; Fukuda et al, 1985, 1993; Gao et al, 2016; M. Ismail & Choudhary, 2016; Kim et al, 2019; Lam et al, 2018, 2012; Li et al, 2004a, 2004b; Pachaly et al, 1992; Thomas et al, 2016; Van Kiem et al, 2010; Xu et al, 2017; Yonemitsu et al, 1995; Y. Zhang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2667 features were detected in both positive and negative ionization modes. By analyzing the MS1 and MS1 mass spectra of the analyte peaks, 58 metabolites were successfully identified using data from previous studies and databases (Table 2) (Ahmad et al, 2016; Bowen & Motawe, 1985; Choudhary, Ismail, Ali, et al, 2010; Choudhary, Ismail, Shaari, et al, 2010; Dong et al, 2010; Fukuda et al, 1985, 1993; Gao et al, 2016; M. Ismail & Choudhary, 2016; Kim et al, 2019; Lam et al, 2018, 2012; Li et al, 2004a, 2004b; Pachaly et al, 1992; Thomas et al, 2016; Van Kiem et al, 2010; Xu et al, 2017; Yonemitsu et al, 1995; Y. Zhang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Their structures are constructed with phenylpropane units and majorly classified into furofuran, furan, dibenzylbutane, and arylnaphthalene groups [ 18 , 20 ]. Our previous works showed the anti-neutrophilic activities of furofuran, furan, and arylnaphthalene lignans [ 60 , 61 , 62 , 63 , 64 ]. Here, we found MDGA, a dibenzylbutane-type lignan, not only exhibited greater anti-neutrophilic ability than previous lignans but also attenuated various neutrophilic functions induced by GPCR agonists.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, due to the complexities and diversities of its chemical constituents, the effective constituents and their molecular mechanisms for its anti-arthritis effect are still poorly understood. 6,7 According to the previous report, the EtOAc fraction of ethanolic extract from the stems of T. sinensis exhibited an anti-arthritis effect, which might be attributed to inhibiting the production of pro-inammatory cytokines and down-regulating the MAPK signaling pathway, and suggested that avonoids including rutin, quercetin and isorhamnetin might be the mainly effective constituents in the crude extracts. 3 But actually, the chemical compositions of T. sinensis were very complicated, which contained terpenoids such as sesquiterpenoids, diterpenoids and triterpenoids, lignans, alkaloids, avonoids and so on.…”
Section: Introductionmentioning
confidence: 98%
“…6 Among them, diterpenoids and lignans were abundant in T. sinensis. Therefore, in order to have a fully understanding of these two classes of compounds in T. sinensis, a phytochemical reinvestigation of T. sinensis was undertaken, resulting in the isolation of twenty-two compounds, including sixteen lignans (1-2, 9-22) and six clerodane diterpenoid glucosides (3)(4)(5)(6)(7)(8). Among them, compound 1 was a previously undescribed tetrahydrofuran lignan, and compound 2 was a previously undescribed 7,9 0 -dinorlignan glucoside.…”
Section: Introductionmentioning
confidence: 99%